Blue nevus with a starburst pattern on dermoscopy - Shiga, Takeo (Derm101.com, 2012)
An 11-year-old girl presented to our department with a blue-gray papule approximately 4 mm in diameter. We suspected that it was a blue nevus or a pigmented Reed/Spitz nevus. On dermoscopic observation, the lesion showed homogeneous black-bluish pigmentation. This dermoscopic feature was suggestive of a blue nevus. However, near-circumferential streaks and a global feature of a “starburst pattern” were also observed, as is often found in a Reed/Spitz nevus. The lesion was excised and histological examination revealed spindle cells with melanin pigments diffusely present in the upper dermis and around hair follicles in the mid-dermis, but not in the epidermis. The melanocytic cells were arranged in a symmetrical wedge-shaped configuration. In addition, there was a diffuse fibrosis. Finally, we made a diagnosis of a blue nevus based on these findings.